Association between phase angle from bioelectrical impedance analysis and level of physical activity: Systematic review and meta-analysis. Issue 4 (August 2019) - Mundstock, Eduardo; Amaral, Marina Azambuja; Baptista, Rafael R.; Sarria, Edgar E.; dos Santos, Rejane Rosaria Grecco; Filho, Adriano Detoni; Rodrigues, Carlos Alberto S.; Forte, Gabriele Carra; Castro, Luciano; Padoin, Alexandre Vontobel; Stein, Ricardo; Perez, Lisiane Marçal; et al.
Summary: Objective: To evaluate the relationship between physical activity and phase angle. Design: Systematic Review and Meta-analysis. Data sources: Electronic searches of MEDLINE (via PUBMED), EMBASE, Cochrane Central Register of Controlled Trials (CENTRAL, The Cochrane Library), SciELO, LILACS, SPORTDiscus, Scopus, and Web of Science from inception to December 10th, 2017. Eligibility criteria for selecting studies: The PICOS strategy was defined, in which "P" corresponded to participants of any age, sex or ethnicity, "I" indicated any type of physical activity program, "C" denoted lack of exercise or irregular physical activity, "O" corresponded to the phase angle obtained by bio-impedance, and "S" indicated longitudinal or cross-sectional studies. Results: In cross-sectional studies the phase angle was higher among the active individuals (MD = 0.70; 95% CI: 0.48, 0.92, P  < 0.001), with low heterogeneity (I 2  = 0%; P  = 0.619). In longitudinal studies, the mean of the difference of phase angles from the baseline was significantly higher for the active group than the control group (MD = 0.30; 95% CI: 0.11, 0.49, P  = 0.001), with low heterogeneity (I 2  = 13%, P  = 0.331). No evidence of publication bias was found and the overall risk of bias was moderate to high. Summary/conclusion: The positive association of physical activity with phase angle reinforces the importance of routinely including exercise in health care. We also identified the need for further studies to define with different types, intensities and frequencies of exercises should be conducted in order to find the best dose-effect relationship.